Immunology & Immune System - Alack K; Pilat C; Krüger K (Deutsche Zeitschrift für Sportmedizin, 2019)
Exercise has a signifi cant effect on the regulation of the immune system. Acute bouts of exercise induce an intensity-dependent leukocytosis, followed by redistribution of e ector cells into peripheral tissues. ese processes are a result of the activation of the sympathetic nervous system and the hypothalamic-pituitary-adrenal axis, increased hemodynamics, and the release of stress hormones such as catecholamines and glucocorticoids.During periods of intensive training, athletes frequently report increased symptoms of upper respiratory tract infections (URTI) which may be a result of a stress overload associated with an impairment of mucosal immunity. In contrast, single bouts of short-term or moderate intensity as well as regular exercise training are mainly immuno-enhancing. In this regard, exercise positively a ects the composition of the T cell compartment and the function of various leukocyte subpopulations. Regular exercise of moderate intensity also exerts immune-regulating e ects during in ammation-associated diseases, such as obesity, type 2 diabetes, or cardiovascular diseases, and counteracts hallmarks of immunosenescence. Consequently, exercise represents a powerful behavioral intervention that has the potential to improve both immune function and health outcomes in subjects of all ages in prevention and therapy. e present review summarizes the current knowledge, new challenges and future directions in the eld of exercise immunology.KEY WORDS: Infl ammation, Physical Activity, Lymphocytes, Mucosal Immunity, Neutrophils, NK Cells